Minute-cadence Observations of the LAMOST Fields with the TMTS. VI. Physical Parameters of Contact Binaries - Qiqi Xia; Xiaofeng Wang; Kai Li; Xiang Gao; Fangzhou Guo; Jie Lin; Cheng Liu; Jun Mo; Haowei Peng; Qichun Liu; Gaobo Xi; Shengyu Yan; et al. (The Astronomical Journal)
With the development of wide-field surveys, a large amount of data on short-period W UMa contact binaries have been obtained. Continuous and uninterrupted light curves as well as high-resolution spectroscopic data are crucial in determining the absolute physical parameters. Targets with both TMTS light curves and LAMOST medium-resolution spectra were selected. The absolute physical parameters were inferred with the W-D code for 10 systems, all of them are W-type shallow or medium contact binaries. The O'Connell effect observed in the light curves can be explained by adding a spot on the primary or secondary component in the models. According to O − C analysis, the orbital periods exhibit a long-term increasing or decreasing trend, among which J0132, J1300, and J1402 show periodic variations that may be attributed to the presence of a third body or magnetic activity cycles. Spectral subtraction analysis revealed that the equivalent width of H α indicates strong magnetic activity in J0047, J0305, J0638, and J1402. Among the 10 selected binary systems, except for J0132 and J0913, the more massive components are found to be main-sequence stars while the less massive components have evolved off the main sequence. In J0132, both components are in the main sequence, whereas both components of J0913 lie above the terminal-age main sequence. Based on the relationship between orbital angular momentum and total mass for these two systems, as well as their low fill-out factors, it is possible that these two systems are newly formed contact binaries, having recently evolved from the detached configuration.